Plan de marketing para la lavadora y lubricadora Reina del Cisne de la ciudad de Yanzatza, provincia de Zamora Chinchipe - Chamba Campos, Kerlly Maricela (2014)
The objective of this work is to design a MARKETING PLAN FOR THE WASHER AND LUBRICATOR SWAN QUEEN CITY Yanzatza, PROVINCE OF ZAMORA CHINCHIPE, and thus it is intended that the company maintain and improve its operation in his service , promising to be competitive efficient and satisfying customer needs . Different methods as deductive, analytical, Synthetic, Mathematical and Statistical that allowed collect more relevant to later use in the present analysis information and who helped design the Marketing Plan for the machine was used for the realization of this thesis project and lubricator, it will be suggested to the Manager - Owner for its implementation and commissioning. To start an interview was applied to the Manager - Mr. Lorenzo Cave Owner Simancas, a survey of each of the three real customers and 120 employees Washer and lubricator, being the sample size of this investigation, information obtained allowed us to visualize the current structure of the organization and its market position . In the External Analysis was achieved identify opportunities and threats in the Matrix External Factors Evaluation ( EFE ) a total weight of 2,92 was obtained, concluding that there is a predominance of opportunities over threats. For Internal Analysis, an interview with Manager - Owner, surveys of 3 employees and 120 real clients, each with its quantitative representation, analysis and interpretation was performed, thus ensuring obtaining worthwhile results of the strengths and weaknesses who served for developed Matrix internal Factors evaluation ( EFI ) obtaining the weighting 3,05, being the internal strategic position of the washer and lubricator as a strong internally. With the identification of these variables proceeded to conduct the Study SWOT Analysis by Matrix Combination of Factors, so we can formulate strategic objectives, which served as the basis for generating the proposal will contribute to improving the functioning washer and lubricator Swan Queen city Yanzatza; given that it is aimed at:  Implement a training plan for operational and administrative staff of the company, at a cost of $ 461.20.  Design the Logo and Slogan for the company to achieve identified competition with implentación cost of $ 247.00.  Implement a Plan Advertising and Promotion to improve the positioning of the company, at a cost of $ 1,543.00.  Perform agreements with public and private institutions for better organization in providing the service, at a cost of $ 110.00.  Implement charges in the washer and lubricator to achieve better results in the execution of tasks, with a cost of $ 17.50.  Renew working tools to improve service quality and achieve customer satisfaction, at a cost of implemntación of $ 9,127.82 . Further conclusions and recommendations that will improve the quality of service, thereby better positioning and recognition in the local market were determined.